The relationship between apolipoprotein genes polymorphisms and susceptibility to osteonecrosis of the femoral head: a meta-analysis - Yangquan Hao; Hao Guo; Zhaochen Xu; Handeng Qi; Yugui Wang; Chao Lu; Jie Liu; Puwei Yuan (Lipids in Health and Disease, 2018)
Abstract Background The objective of this study was to evaluate whether apolipoprotein gene polymorphisms confer susceptibility to osteonecrosis of the femoral head (ONFH). Methods The relevant literature was screened from databases of Pubmed, Embase, Wanfang, Weipu and China National Knowledge Internet (CNKI) until May, 2017. In addition, odds ratio (OR) and its corresponding 95% confidence interval (CI) were used as a measure of effect size for calculating effect size. Results Totally, six case-control studies were included in this meta-analysis. It revealed that ApoB-C7623T polymorphism frequency was increased in ONFH group than in control group under three genetic models, including allele model (T vs. C, OR = 4.5149, 95% CI: 1.6968–12.0134); additive model (TC vs. CC, OR = 6.2515, 95% CI: 2.0939–18.6640); and dominant model (TT + TC vs. CC, OR = 5.4998, 95% CI: 1.9246–15.7163). In addition, the increased risk of ONFH were related to ApoA1-rs1799837 polymorphism under additive model (AA vs. GG, OR = 1.4175, 95% CI: 1.0522–1.9096) and recessive model (AA vs. GG + AG, OR = 1.7727, 95% CI: 1.3399–2.3452). However, four ApoB rs1042031, rs693, 3’-VNTR and G12619A polymorphisms under the all genetic models were not associated with susceptibility to ONFH. Conclusion The T allele and TC genotype of ApoB-C7623T and AA genotype of ApoA1-rs1799837 may contribute to increase the risk of ONFH.